A model to analyse financial fragility: applications - Goodhart, Charles A.E.; Sunirand, Pojanart; Tsomocos, Dimitrios P. (Journal of Financial Stability, 2004)
The purpose of our work is to explore contagious financial crises. To this end, we use simplified, thus numerically solvable, versions of our general model [C.A.E. Goodhart, P. Sunirand, D.P. Tsomocos, A Model to Analyse Financial Fragility, Oxford Financial Research Centre Working Paper No. 2003fe13, 2003]. The model incorporates heterogeneous agents, banks and endogenous default, thus allowing various feedback and contagion channels to operate in equilibrium. Such a model leads to different results from those obtained when using a standard representative agent model. For example, there may be a trade-off between efficiency and financial stability, not only for regulatory policies, but also for monetary policy. Moreover, agents who have more investment opportunities can deal with negative shocks more effectively by transferring ‘negative externalities’ onto others.